Guidance on using the revised Logical Framework - How to note - and DFID (DFID, 2011)
The principal changes to the logframe from the earlier (2008) 4 x 4 matrix are: - Objectively Verifiable Indicators (OVIs) have been separated into their component elements (Indicator, Baseline and Target), and Milestones added. - Means of Verification has been renamed ‘Source’. - Inputs are now quantified in terms of funds (expressed in Sterling for DFID and all partners) and use of DFID staff time (expressed as annual Full-Time Equivalents (FTEs). - A DFID Share box now indicates the financial value of DFID’s Inputs as a percentage of the whole. - Assumptions are shown at Purpose and Output level only. - Risks are shown at Activities level only, but also rated at Output level; - At the Output level, the Impact Weighting is now shown in the logframe together with a Risk Rating for individual Outputs. - Activities are now shown separately (so do not normally appear in the logframe sent for approval), although they can be added to the logframe if this is more suitable for your purposes. - A renewed emphasis on the use of disaggregated beneficiary data within indicators, baselines and targets. The Logical Framework (logframe) was significantly re-designed in February 2009. In January 2011 a slightly amended logframe template was introduced at the same time as the launch of the new DFID Business Case. Given the extent of changes that took place in February 2009 it was only necessary to make minor amendments in January 2011. These amendments are as follows: - Results Chain terminology aligned across DFID (the terms Goal and Purpose in the old logframe template have been replaced by Impact and Outcome) - Rows added to allow achieved results to be captured alongside the planned results determined at project design stage - Word version of the logframe template removed – excel is the preferred format for logical frameworks from January 2011 - Indicator numbering introduced within logframe template